Digital transformation as a function of rural tourism strategic development in the Republic of Croatia - Ivona Vrdoljak Raguž; Monika Hordov; Mladen Rajko (Ekonomski Vjesnik)
Purpose: The research, which holds significant importance, analyzes the key factors influencing the digital transformation in the strategic development of rural tourism in the Republic of Croatia. It aims to determine the impact of county locations, categorized into clusters: Adriatic Croatia, Continental Croatia, and Slavonia-Baranja. The study aims to investigate specific factors that support sustainable digital transformation in rural areas, which is a topic of increasing interest and relevance. Methodology: Primary data were collected through survey questionnaires sent to relevant stakeholders in rural areas. The analysis was carried out using the Kruskal-Wallis test in the Jamovi application to assess the influence of an ordinal variable (location) on the factors of digital transformation, including external, technological, organizational, and socio-demographic factors. Results: The results show significant differences among the clusters: Continental Croatia and Adriatic Croatia highlighted the importance of external factors (e.g., economic support) and technological factors (e.g., IT infrastructure), respectively, while socio-demographic factors were identified as key factors in the Slavonia-Baranja cluster. These findings confirm the need for a tailored regional approach. Conclusion: The research conclusions underscore the practical implications of the identified factors for stakeholders in designing sustainable digitalization models. These findings can serve as actionable guidelines, equipping stakeholders with the necessary insights to increase the engagement of the local community in the digital transformation in the strategic development of rural tourism in Croatia. While the research acknowledges limitations, such as sample size and the subjectivity of responses, the results provide a valuable contribution to future research and the policy of digitalization of rural tourism strategic development in Croatia.